Stevens-Johnson Syndrome (SSJ) and Toxic Epidermal Necrolysis (TEN) - Mega Asri Dhamasari, Putu; Salsabilla, Rani; Ramadhan, Ath-Thariq (Rifa'Institute, 2021)
Stevens-Johnson syndrome (SSJ) and toxic epidermal necrolysis (TEN) are acute, rare, and potentially fatal type IV (Subtype C) skin hypersensitivity reactions that cause skin loss and in some cases may result in loss of mucous membranes followed by systemic symptoms. In general, the incidence of SJS is 1-6 cases/million population/year, and the incidence of NET is 0.4-1.2 cases/million population/year. SJS and TEN are considered to be on the same disease spectrum with different degrees of severity. The exact cause of SJS is currently unknown, but several things have been found that can trigger SJS, such as drugs or viral infections. A collection of symptoms (syndromes) in SJS and TEN in the form of abnormalities characterized by erythema, vesicles, bullae, purpura on the skin at the mouth of the body cavity which has mucous membranes and eyelid mucosa. The success of SJS treatment is largely determined by early recognition of symptoms, stopping or overcoming the causative factors, and providing adequate supportive therapy. A literature review discusses and analyses published information in a particular subject area. Sometimes the information covers a certain time period. Syndrome Stevens-Johnson (SSJ) and nekrolisis epidermal necrolysis (NET) is a hypersensitivity reaction type IV (subtype C) skin that is acute, rare, and potentially fatal cause loss of skin and in some cases can result in its loss of mucous membranes followed by systemic symptoms